Two new species of the genus Chelidoperca (Perciformes: Serranidae) from the Andaman Sea, eastern Indian Ocean - Psomadakis, Peter N.; Gon, Ofer; Htut, Thaung (Zootaxa, 2021)
Two new species of the genus Chelidoperca are described from specimens collected in 2015 and 2018 from the Andaman Sea, off the coast of Myanmar during trawl bottom surveys conducted by the R/V Dr. Fridtjof Nansen. Chelidoperca myathantuni sp. nov. is described based on 15 specimens (74.3–129.5 mm SL) from 101–185 m depth, which can be distinguished from all congeners by the following combination of characters: 3 (2 full-sized plus 1 half-sized) scale rows between lateral line and middle of spinous dorsal-fin base; 42–44 (modally 44) pored lateral-line scales; 16 pectoral-fin rays; interorbital scales extending to mid-orbit level; scales on ventral surface of lower jaw restricted to the angular (not extending onto the dentary); enlarged caniniform teeth on the upper jaw; side of body with longitudinal dashed black stripe; dorsal fin pale yellow with reddish pigment mostly restricted at base of spines and rays. Chelidoperca flavimacula sp. nov. is described based on eight specimens (49.7–70.7 mm SL) from 84–131 m depth, which can be distinguished from all congeners by the following combination of characters: 3 (2 full-sized plus 1 half-sized) scale rows between lateral line and middle of spinous dorsal-fin base; 42–45 (modally 42) pored lateral-line scales; 9–10 (modally 10) scale rows below the lateral line; 6 predorsal scales; 16–17 (modally 16) circumpeduncular scales; 5 scales rows on cheek; interorbital scales extending to mid-orbit level; anal fin with yellowish distal margin and three or four rows of bright yellow spots over its proximal half.